REDD and international organizations - Valentina Giannini (Fondazione Eni Enrico Mattei (FEEM), 2010)
Climate change mitigation can be achieved, according to many, by means of Reducing emissions from deforestation and forest degradation in the Tropics (REDD). Within the climate change policy debate we thus find discussions on how to reduce GHG emissions by designing appropriate REDD programmes and projects. In this paper I try to capture this debate by looking at the role of five major international organizations, which were chosen to represent the different aspects related to REDD. In order for REDD to be successful, not only GHG reduction, but also multiple benefits should be achieved: indigenous and local peoples' involvement, livelihood improvement, fair and equitable labour, biodiversity conservation, and sustainable forest management, to name some of the most relevant. The selected international organizations are: UN-REDD, The GEF, The CBD, ITTO, and ILO. The role of these is assessed, to understand not only what has been defined and achieved, but also what possible way forward the organizations are envisioning, and what issues remain to be addressed.
Keywords: O13; O20; Q23; Q28; Q54; Q56; Q57; 330; Reducing Emissions from Deforestation and Forest Degradation; REDD; Climate Change; Climate Policy Debate; Mitigation; Multiple Benefits; UN-REDD; The GEF; The CBD; ITTO; ILO